Novel Variance Based Spatial Domain Watermarking and Its Comparison with DIMA and DCT Based Watermarking Counterparts - Megalingam, Rajesh Kannan; Nair, Mithun Muralidharan; Srikumar, Rahul; Balasubramanian, Venkat Krishnan; Sarma, Vineeth Sarma Venugopala (IntechOpen, 2011)
None